Considerations for design and implementation of vaccine field trials for novel foot-and-mouth disease vaccines. Issue 8 (14th February 2019) - Lyons, Nicholas A.; Knight-Jones, Theodore J.D.; Bartels, Chris; Paton, David J.; Ferrari, Giancarlo; Vermillion, Meghan S.; Brooks, Abdullah W.; Motroni, Roxann; Parker, Elizabeth; Hefferin Berquist, Melissa L.; Sumption, Keith J.; Klement, Eyal
Abstract: Vaccines are commonly used to control Foot-and-Mouth Disease (FMD) in endemic regions and form an important part of contingency plans for FMD-free countries. Conventional FMD vaccines have numerous limitations, and the U.S. government supports the development of next-generation vaccines. In the U.S., vaccine efficacy is typically demonstrated through experimental vaccination and challenge of animals using the World Organization for Animal Health (OIE) standards. Although conventional challenge and immunogenicity studies provide useful information, they have limitations and results do not always accurately predict field performance. Consequently, there is a need to test next-generation vaccines under field conditions to gain a better understanding of field performance to inform policy decisions and support their viability as a commercial product. In June 2017, an expert consultation was organised to discuss and define an optimal field study design for novel FMD vaccines. Cattle were the primary species considered, although parallel strategies for swine and small ruminants were also discussed. Many methodological and logistical considerations in the study design were identified, including: (1) study site selection and the importance of baseline studies to understand exposure risk, (2) ethics of using a placebo and assessing equivalence with conventional vaccines, (3) merits of using individual randomised versus cluster randomised trials, (4) preventive versus reactive vaccination, and (5) methods of randomisation and blinding. The proposed optimal study design was a multicentre (i.e. farm), three-arm, double-blind randomised controlled trial comparing groups receiving the novel vaccine to a conventional vaccine group and a placebo group. Large farms in areas of high exposure risk were identified as ideal study sites, and the primary study outcome was susceptibility to disease or infection, during a six-month observation period, following a single dose of vaccine. This report provides a summary of the important issues to consider when designing a field efficacy study in livestock and proposes a study design that could be utilised for novel FMD vaccines.